Sequence analysis of S1 gene of Malaysian infectious bronchitis virus variant and QX-like strains following serial passage in specific-pathogen-free embryonated chicken eggs - Ismail, Mohd Iswadi; M., Suwaibah; Tan, S. W.; Bejo, Mohd Hair; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
Infectious bronchitis virus (IBV) causes infectious bronchitis (IB) disease in chickens is primarily a disease associated with respiratory tract. However, depending on virus strains, IBV can also infect the gut, reproductive and kidney of chickens. Controlling the disease is problematic because of the presence of diverse serotypes and strains, and poor cross-protection against different serotypes/strains. Recently, we have characterized the IBV strains circulating in Malaysia. Two of the prevalent strains, Malaysian local variant (MLV) (IBS037A/2014) and QX-like (IBS130/2015) were attenuated by serial passage of the virus in SPF embryonated chicken eggs. The virus strains at different passages were characterized based on sequence analysis of the partial S1 gene. Overall, IBS130/2015 showed a higher number of nucleotide and amino acid variations compared to IBS037A/2014 following serial passage in embryonated chicken eggs.